2017
DOI: 10.1007/s10147-017-1162-6
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative radiotherapy for extremity soft-tissue sarcomas: can long-term local control be achieved?

Abstract: IOERT used as a boost to EBRT provides high local control and limb-sparing rates in patients with STS of the extremities, with less toxicity than EBRT alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Our experience matches other series in terms of low severe toxicity rates. Across the many IOERT experiences, Grade 3 late toxicity ranged from 10%–31% 12,13,21–24,30–35 . In our series, we demonstrated low Grade 3 late toxicity; fracture requiring surgical fixation occurred within 7 (6%) patients and severe neuropathy occurred in only 1 (1%) patient within our cohort.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Our experience matches other series in terms of low severe toxicity rates. Across the many IOERT experiences, Grade 3 late toxicity ranged from 10%–31% 12,13,21–24,30–35 . In our series, we demonstrated low Grade 3 late toxicity; fracture requiring surgical fixation occurred within 7 (6%) patients and severe neuropathy occurred in only 1 (1%) patient within our cohort.…”
Section: Discussionmentioning
confidence: 54%
“…Across the many IOERT experiences, Grade 3 late toxicity ranged from 10%-31%. 12,13,[21][22][23][24][30][31][32][33][34][35] In our series, we demonstrated low Grade 3 late toxicity; fracture requiring surgical fixation occurred within 7 (6%) patients and severe neuropathy occurred in only 1 (1%) patient within our cohort. However, there were 11 (10%) patients who had 21 The same group reported data on 50 patients in a prospective trial, which shows an 18% late severe toxicity rate in addition to excellent control rates.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…While 50% of patients with involved margins had local recurrence, only 7% of those with negative margins had recurrence. They concluded that local control was excellent, and side effects were acceptable (10). IORT provides an excellent chance to irradiate the tumor bed or residue and spare the sensitive tissues.…”
Section: Discussionmentioning
confidence: 99%